Contemporary Spirituality and the Making of Religious Experience: Studying the Social in an Individualized Religiosity - Versteeg, Peter Gerrit Albert (Fieldwork in religion, 2011)
The turn to experience' has been described as one of the most defining characteristics of contemporary religion. Research on religion, and in particular on spirituality, therefore increasingly concentrates on the description of its experiential dimensions. The turn to experience, however, asks for something more than just the observation that a particular dimension (experience) has become of greater value for practitioners of religion. Dimensions which have for a long time been central to the social-scientific study of religion, but are avoided in the practitioners' discourse and, surprisingly, in the social-scientific discourse as well, such as authority and power, turn out to be of lasting significance in the mediation and construction of religious experience. In this contribution, the authors take the social construction of religious experience in contemporary spirituality as a starting point for a reflection and discussion on the methodological challenges of experiential religion for those engaged in the study of religion.